USING THE CANVA APPLICATION IN LEARNING TO COLLECT PRINT MEDIA ADVERTISING TEXT IN CLASS V ELEMENTARY SCHOOL - widdy rorimpandey; Ayomi Fatwa (Universitas Negeri Surabaya, 2023)
This study aims to describe the provisions in the process of accepting students with disabilities in inclusive schools. This research was conducted with a descriptive qualitative research approach. Data collection was carried out by interview, observation, and documentation techniques. Interviews were conducted with special supervising teachers, counseling teachers, and parents of students with disabilities. Data analysis using the Miles and Huberman technique includes data reduction, data display, and drawing conclusions. The validity of the data was tested by triangulation of sources and techniques. The results of the research show that there are different terms or conditions in the process of accepting students with disabilities in inclusive schools. The provisions are that prospective students bring an assessment document stating that the child is disabled, a minimum IQ test result of 75, types of disabilities that are acceptable and those that the school is able to serve are students with disabilities with mild types of disabilities.